EFFECTS OF LABOR LAW AT THE REGULATION OF PUBLIC SERVANTS - Velichko L.Yu. (Pressing Problems of Public Administration, 2017)
The article is devoted to the question of the scope of labour law to regulate the work of civil servants. The author examined the positions of scientists, legislative provision and the jurisprudence on the subject, came to the conclusion that the relations in the sphere of work of civil servants are in the scope of labor law, but given the nature of their work, duties assigned to them,  rst of all, in respect of the official functions of public of cials and their responsibility.